Charting Morphotoxicity With Complementary Embryo Models - Dorian G. Luijkx; Pauline L. Balder; Romy M. L. Verhagen; Vinidhra Shankar; Barry Jutten; Pinak Samal; Timo Rademakers; Clemens A. van Blitterswijk; Stefan Giselbrecht; Erik J. Vrij (Advanced Healthcare Materials, 2026)
ABSTRACT Understanding developmental toxicity demands capturing the full spectrum of morphological diversity, or morphospace, that defines early human embryogenesis. Traditional toxicity testing methods, relying on animal models or simplified 2D cell cultures, inherently overlook the nuanced interplay between distinct developmental stages and cell lineages. Addressing this gap, we present an innovative high‐throughput screening approach leveraging three complementary 3D stem cell‐based embryo models: preimplantation stage blastoids, and early postimplantation stage epiblast‐like (EPICs) and amnion‐like clusters (AMNICs). Cultured in thermoformed microwell arrays, these models were systematically exposed to a library of 27 widely used compounds. Automated image‐based analyses allowed for precise quantification of morphotoxic effects. Key findings include the identification of compounds such as ascorbic acid and valproic acid (VPA), which demonstrated distinct and opposing effects across the different embryo models, highlighting developmental stage‐specific sensitivities. This integrative platform underscores the essential role of complementary embryo models to achieve robust and human‐relevant developmental toxicity assessment.